Nanoscale mapping of the subcellular glycosylation landscape - Schröter, Helene Gregoria; Saß, Steffen; Heilemann, Mike; Kuner, Thomas; Klevanski, Maja (Advanced science, 2026)
Glycosylation is a crucial biochemical modification of proteins and other biomolecules in cells that generates an exceptional structural and functional diversity. Aberrant glycosylation is implicated in numerous diseases, including neurodegenerative disorders and cancer. While glycan organization at the cell surface is studied extensively, the nanoscale spatial arrangement of glycans inside cells and within organelles remains largely unexplored. Here, super-resolution imaging with fluorophore-labeled lectins, combined with a dedicated multiplexing strategy (Glyco-STORM), was used in thin neuronal tissue sections and permeabilized cells to systematically map glycosylation across multiple organelles and cellular compartments. Lectin markers were identified that enabled the visualization of nanodomains within the endoplasmic reticulum, subdomains along the Golgi axes, diverse glycosylation states in the endolysosomal system, and a polarized lysosomal clathrin coat. At neuronal synapses, mature glycans were found to demarcate the synaptic cleft and subsynaptic tubules adjacent to the postsynaptic density. In summary, Glyco-STORM establishes one of the first comprehensive nanoscale maps of intracellular glycosylation and provides entry points into health- and disease-related studies.
Online verfügbar: 10. November 2025
Gesehen am 27.02.2026